The Influence of Student Background Characteristics on Proficiency in English as a foreign language: Indonesian Context - Ratna Rintaningrum; Carol Aldous; John P Keeves (Jurnal Sosial Humaniora, 2017)
In order to explain differences in English proficiency level, one needs toconsider a number of factors frequently considered important at a variety oflevel of education systems. Among the factors that operate to influenceEnglish Foreign Language Proficiency are those associated with the studentbackground variables. This study identifies the student level factors thatinfluence English Foreign Language Proficiency. It is expected that this studycan contribute to the development of a theory of foreign language learningthat applies to students studying the English language at other universities inIndonesia and South-East Asia. This study involves the employment of anexploratory approach for the examination of the relationships betweenvariables operating at the student level. Data are analyzed using PartialLeast Squares Path Analysis (PLSPATH) to identify in an exploratory waythe variables that have significant direct and indirect effects on EnglishForeign Language Proficiency. The study shows that a number of studentbackground characteristics such as sex of student (GENDER), socioeconomic of student (SES), Faculty of Instruction (FACULTY), score ofEnglish 1 (ENGLISH_1) and semester in which students enrol in English 2(SEMESTER) have only direct effects on English Language Proficiency,while student prior achievement (PRIOR) has both direct and indirect effectson English Foreign Language Proficiency.